Proceedings. IEEE Conference on Advanced Video and Signal Based Surveillance, 2005.
DOI: 10.1109/avss.2005.1577265
|View full text |Cite
|
Sign up to set email alerts
|

A real time surveillance system for metropolitan railways

Abstract: This paper presents a real time surveillance system that can be deployed within public transport environments. The system is a fully customisable application that can be used to address the requirements for this application domain. The system has been under trial on a number of metropolitan railway systems in the UK and Italy. In this paper we discuss how some of the algorithms employed within the system can be adapted for use with the CREDS datasets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Chauhan et al proposed a moving object detection method that combines a GMM-based background difference and optical flow to compensate for the disadvantages of typical motion estimation based methods and background difference-based methods [13]. Additional research on the visual surveillance techniques can be found in [14][15][16][17][18][19][20].…”
Section: Related Workmentioning
confidence: 99%
“…Chauhan et al proposed a moving object detection method that combines a GMM-based background difference and optical flow to compensate for the disadvantages of typical motion estimation based methods and background difference-based methods [13]. Additional research on the visual surveillance techniques can be found in [14][15][16][17][18][19][20].…”
Section: Related Workmentioning
confidence: 99%
“…[5,6,8]. To detect abrupt and dangerous situations, object tracking has been implemented using a combined method of background subtraction, edge detection and motion detection [9][10][11][12][13][14]. An infrared camera was found to be useful to locate passengers [10].…”
Section: Introductionmentioning
confidence: 99%
“…These systems are focused on measuring the level of crowding on the passenger platforms of train services. If overcrowding is detected, the system will notify the station operators to take appropriate actions to prevent dangerous situations such as people falling off or being pushed onto the tracks [9][10][11][12][13][14]. Background subtraction is commonly used to locate passengers and thereby to estimate the crowd density [1][2][3][4][5]7] Edge information may be used to measure the regions occupied by passengers [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Four final candidates have successfully submitted their solutions to the specific event detection tasks described in Section 2 and have accepted to follow the performance evaluation procedure described in Section 4. The four proposals are described in detail in [1], [2], [3] and [4].…”
Section: Proposals Submitted To Credsmentioning
confidence: 99%
“…In [2], a block based motion estimation approach is used in a statistical framework to robustly generate background estimation. Foreground segmentation benefits from the robustness of the background and enables the approach to detect several events of interest.…”
Section: Proposals Submitted To Credsmentioning
confidence: 99%